Magic Mouthguards and Primary Oral Health Care–Evidence for Policy Makers - Ihimaera, CN; Silcock, EM; Tuohy, J (The New Zealand Dental Association, 2026)
The World Health Organization (WHO) advocates for diverse evidence in effective health policy development and practice. This paper describes the ‘Magic Mouthguard’ initiative, an innovative oral health collaboration between a university, a corporate sponsor, and a public high school rugby team. Primarily aimed at injury prevention, the team’s international triumph created unforeseen association between the mouthguards and their athletic achievement. The ‘magic’ of these mouthguards lead to communal uplift derived from feeling cared for and invested in, potentially contributing to the rugby team’s victory. The initiative also advanced equitable access to custom-fitted mouthguards while confronting a systemic inequity by providing oral health treatment to young athletes who often face barriers to accessing oral healthcare, especially within a Māori and Pasifika communities in Aotearoa New Zealand. The story illustrates healthcare innovation by demonstrating that settings are integral to healthcare delivery and trust is foundational for engagement. This highlights how leveraging embedded knowledge and diverse evidence can integrate into oral health practice and promote population-level health.
Keywords: 1105 Dentistry; Dentistry; 3203 Dentistry